2023
DOI: 10.14710/genres.v3i1.17272
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas Antioksidan Kombinasi Ekstrak Etanol Jahe (Zingiber officinale Roscoe.) dan Daun Jeruk Purut (Citrus hystric Dc.)

Abstract: Tanaman herbal jahe (Zingiber officinale) dan daun jeruk purut (Citrus hystrix) memiliki kandungan senyawa antioksidan berupa flavonoid, fenol, dan terpenoid. Penelitian bertujuan mengetahui aktivitas antioksidan (efek dan nilai aktivitas antioksidan terkuat) dari kombinasi jahe dan daun jeruk purut. Penelitian meliputi determinasi, pembuatan, dan karakterisasi simplisia, ekstraksi etanol 96% (1 : 10) metode ultrasonik, skrining fitokimia, dan uji aktivitas antioksidan. Uji aktivitas antioksidan menggunakan me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The study by Mustafa & Chin (2023) showed that ethanol extracts had the best free radical scavenging activity with IC50 values < 50 µg/mL, with IC50 values of 15.23 µg/mL for sun-dried ginger samples and 22.10 µg/mL for oven-drying. The ultrasonic approach produced an extract from ginger that had a very high antioxidant capacity and an IC50 value of 51.46 0.31 µg/mL (Sarastri et al, 2023). There were the same strength categories for antioxidant ability: very strong antioxidant ability.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The study by Mustafa & Chin (2023) showed that ethanol extracts had the best free radical scavenging activity with IC50 values < 50 µg/mL, with IC50 values of 15.23 µg/mL for sun-dried ginger samples and 22.10 µg/mL for oven-drying. The ultrasonic approach produced an extract from ginger that had a very high antioxidant capacity and an IC50 value of 51.46 0.31 µg/mL (Sarastri et al, 2023). There were the same strength categories for antioxidant ability: very strong antioxidant ability.…”
Section: Antioxidant Activitymentioning
confidence: 99%